Happy and Unhappy Days according to Adam Radecki Chamail (1888) - Мишкинене, Галина (Slavistica Vilnensis, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English] This article investigates the text from Adam Radecki Chamail (1888) on happy and unhappy days. The manuscripts of Lithuanian Tatars according to their content are divided into Qur’ans, tafsirs(which contain the text of the Qur’an with an interlinear Polish translation), kitabs (books), chamails(prayer books; there are plenty of folk art, advices on various daily life issues as well as spells in chamails), and tajwids (Qur’an reading rules). The texts about happy and unhappy days are being found only in chamails. The Chamail of Adam Radecki is named after the scribe and is being stored at the Manuscript and Rare Prints Department of the National Library of the Republic of Tatarstan. The national library acquired this manuscript from the resident of Kazan Firdau Kushajeva in 2015. Firdau Kushajeva received the chamail form her uncle. The chamail was rewritten in Belarus (Svislach) and is a part of the Lithuanian Tatar manuscripts’ heritage. It was described for the first time in 2016 by Galina Miškinienė in the journal Безнеӊ мирас. The text, which is being analyzed in the catalogues of Lithuanian Tatars manuscripts, could be assigned to the so-called texts of astrological, calendary and spell-bearing nature. It could be relatively named as Favorable and Unfavorable Days. This text has never been an object of a detailed investigation except for a couple of articles dedicated to one manuscript, namely to the chamail of Aleksandr Aleksandrovich (late 19th century) from the collection of Warsaw. This article presents a detailed description of the text about happy and unhappy days. The researcher uses all so far known and available texts of the same content for the analysis of this text.